Māori perspectives on sleep and aging - Gibson, Rosemary; Lowe, Hannah; Korohina, Erina; Rolleston, Anna (Frontiers in Sleep, 2024)
Introduction Sleep is vital for health in older adulthood. Ethnic disparities have been noted with regards to sleep health. However, culturally appropriate approaches to sleep as a broader social experience are lacking. Methods Here, sleep-related group interviews were conducted in the form of hui (group meetings and discussions) with eleven participants of a health service intervention for older Māori (the Indigenous people of New Zealand) and their whānau (extended family). Notes were collated and analyzed thematically. Results Four key themes were constructed that represent the key conversations and ideas. These concerned the conceptualizing of sleep—including appreciation for its somatic role but also the spiritual properties of sleep states; the changing obligations around sleep and wake—including individual and communal time use and changing cultural and familial obligations with advancing age; and the barriers and facilitators for supporting sleep—including the social and spiritual nature of communal sleeping, the schedules and sleep of others, as well as holistic and environmental methods for relaxation. Findings demonstrate the multifaceted nature of sleep and aging among Māori. Culturally relevant interpretations of sleep practices and disturbances were offered and are beyond typical Western models which are predominantly medicalized. Discussion This work aids the understanding and representation of sleep as a social and cultural perspective within the New Zealand context. This provides foundations for future participatory research to design culturally appropriate approaches to assessing and supporting sleep health in forms that are meaningful for aging well across cultures.